2019
DOI: 10.4257/oeco.2019.2303.17
|View full text |Cite
|
Sign up to set email alerts
|

Stream Fish in the Aripuanã River Upstream and Downstream of the Dardanelos-Andorinhas Waterfall Complex, State of Mato Grosso, Brazil

Abstract: The Aripuanã River basin is part of one of the most biodiverse hydrographic basins on the planet; however, the lack of information on fish diversity in the basin is notable, particularly upstream to the Dardanelos and Andorinhas waterfalls complex. For this study, we sampled 50 m stretches of 71 streams in the Aripuanã River basin, upstream and downstream of the Dardanelos and Andorinhas waterfalls complex. Sampling occurred in the drought period in 2013 and 2014. A total of 11,334 specimens were capture, belo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 22 publications
0
1
0
1
Order By: Relevance
“…Considering that Aripuanã and river Juruena belong to different ecoregions, it is likely to presume that events at regional scale can be the primary driver for the differences observed in this study. Indeed, a recent study has revealed that the Biota Neotrop., 20 (1) Dardanelos and Andorinhas waterfall complex is an important barrier for the fish fauna in the Aripuanã river basin (Silva et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Considering that Aripuanã and river Juruena belong to different ecoregions, it is likely to presume that events at regional scale can be the primary driver for the differences observed in this study. Indeed, a recent study has revealed that the Biota Neotrop., 20 (1) Dardanelos and Andorinhas waterfall complex is an important barrier for the fish fauna in the Aripuanã river basin (Silva et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…É comum que os riachos de uma mesma bacia possuam subconjuntos distintos de espécies, o que resulta da combinação de fatores ecológicos e históricos (p. ex., Ohara & Loeb 2016, Silva et al 2019. Por isso, nem sempre é possível construir um único IBI para uma bacia como um todo (apesar de esta ser a escala desejada), pois, por vezes essa variabilidade é bastante grande e deve ser respeitada na construção do índice.…”
Section: Conclusãounclassified